A Commonsian Reading on Brazilian Unionism - Jeronimo, Rodrigo Constantino [UNESP] (2023)
By systemizing a typology from John R. Commons and John B. Andrews’ discussion about collective bargaining and the attitudes of governments towards labor unions, we present in this article the use of this categorization to investigate the vicissitudes of unionism in Brazil. We do so by analyzing the interaction between the government and labor unions in two different inflection points in Brazil’s labor law history: (i) the Vargas Era (1930–1945) and (ii) the Labor Reform of 2017. Our conclusions relate these periods to the attitudes of “intervention” and “tolerance,” respectively, pointing now to aspects of increasing opposition towards collective action as the economic crisis and unemployment deepen, and new reforms take place.